In vivo profiling and visualization of cellular protein-lipid interactions using bifunctional fatty acids - Haberkant, Per; Sachsenheimer, Timo; Brügger, Britta; Gavin, Anne-Claude; Schultz, Carsten (Angewandte Chemie. International edition, 2013)
Bifunctional lipid technology: Cells convert externally added photoactivatable and “clickable” fatty acids into a variety of bifunctional phospholipids that can be covalently linked to their protein-binding partners by irradiation with UV light. Derivatization of the clickable group with a reporter molecule makes it possible to identify and image the lipid-bound proteins in situ (see scheme).
Gesehen am 03.02.2021